2022
DOI: 10.3390/en15051898
|View full text |Cite
|
Sign up to set email alerts
|

Hourly Simulation of an Earth-to-Air Heat Exchanger in a Low-Energy Residential Building

Abstract: The earth-to-air heat exchanger (EAHE) is a well-founded and verified solution used in modern buildings both for heating and cooling purposes around the world. However, there is a lack of studies on operation of such devices cooperating with ventilation systems of buildings in hourly time step. In this study, the 5R1C thermal network model of a building from EN ISO 13790 was coupled with the EAHE model from EN 16798-5-1 to calculate hourly outlet air temperature. To improve the effectiveness of the considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…For this purpose, the method given in EN 16798-5-1 was used. Simplification assumptions of that model were given and discussed in [35,[53][54][55]. The most important are as follows:…”
Section: Earth-to-air Heat Exchangermentioning
confidence: 99%
See 3 more Smart Citations
“…For this purpose, the method given in EN 16798-5-1 was used. Simplification assumptions of that model were given and discussed in [35,[53][54][55]. The most important are as follows:…”
Section: Earth-to-air Heat Exchangermentioning
confidence: 99%
“…However, in varying ambient conditions (March, April, September, and October) and the thermal demand of the building changing during the day from heating to cooling and vice versa, the effect is not so obvious. Then it seems to be more beneficial to introduce a bypass to switch the intake of ventilation air between EAHE and outdoor air [35,50,51,96].…”
Section: Energy Performance Of the Buildingmentioning
confidence: 99%
See 2 more Smart Citations
“…A longer pipe with a smaller buried diameter having a lower airflow velocity generates an optimal performance of the EAHE system [22]. Michalak et al [23] showed that a study of the operation of a building connected to EAHE model via simple thermal dynamics.…”
Section: Introductionmentioning
confidence: 99%